Management of Residual Refractive Error after Cataract Phacoemulsification. Part 1. Keratorefractive Approaches - K. B. Pershin; N. F. Pashinova; A. Iu. Tsygankov; E. P. Gurmizov; L. V. Batalina (Oftalʹmologiâ, 2017)
The review presents an analysis of the literature data on the methods of surgical correction of residual refractive error after cataract phacoemulsification. Keratorefractive and intraocular approaches are considered in details. A comparison of the efficacy and safety of different groups of methods on the example of comparative studies is given. Historically earlier keratorefractive methods (laser vision correction with LASIK and PRK techniques on intact eyes, LASIK after implantation of multifocal IOLs and arcuate keratotomy after phaco) are indicated for the correction of astigmatic refractive error and a small spherical refractive error. Intraocular methods, including the replacement of the IOL and “piggyback” IOLs implantation are used to correct a large spherical refractive error. The introduction of new technology, the implantation of light-adjustable IOLs, will expand the existing evidence and provide greater predictability and efficiency of the method of correction of residual refractive error.